Operationalizing Maslahah Mursalah: A Six-Stage Methodological Framework for Contemporary Ijtihad - Ahmad Faujih; Marpuah Marpuah; Asep Lukman Hakim; Syahrullah Syahrullah; Fathorrahman Fathorrahman (GHAITSA : Islamic Education Journal, 2026)
This study develops a structured and operational six-stage methodological framework for applying Maslahah Mursalah in contemporary Islamic legal reasoning (ijtihad). A qualitative doctrinal-analytical approach was employed through a systematic examination of classical uṣul al-fiqh sources and contemporary maqāṣid al-sharīʿah scholarship. While previous studies have established the normative legitimacy and contemporary relevance of Maslahah Mursalah, they remain limited in providing an operationalized methodological framework that integrates classical principles into a transparent, replicable, and analytically verifiable sequence of legal reasoning. Addressing this gap, the proposed framework synthesizes al-Shaṭibi’s concept of istiqrāʾ maʿnawī for identifying public benefit, al-Ghazālī’s cumulative validity criteria for legal verification, and Auda’s systems approach for contextual evaluation within a coherent six-stage procedure. The framework is demonstrated through five methodologically representative contemporary legal issues mandatory vaccination, cryptocurrency, surrogate motherhood, environmental protection, and Islamic fintech each representing a qualitatively distinct category of contemporary ijtihādī challenge. Rather than serving as isolated empirical examples, these cases function as methodological archetypes for evaluating the framework across public health, financial innovation, bioethics, environmental governance, and digital finance. The subsequent discussion of citizenship, constitutional democracy, and interreligious social contracts within the framework of al-waṭan wa al-muwaṭanah does not constitute a sixth case study but extends the application of the same methodological model to broader national legal and constitutional contexts. The study contributes an operational methodological model that translates classical legal theory into a transparent, systematic, and replicable process for contemporary Islamic legal reasoning. It concludes that the legitimate application of Maslahah Mursalah depends upon the cumulative fulfillment of classical validity conditions, institutionalized collective ijtihad (ijtihād jamāʿī), and multidisciplinary expert collaboration, thereby strengthening methodological rigor in contemporary Islamic legal decision-making.